Pengembangan Pakan Ternak Bergizi Tinggi dengan Bahan Baku Azolla microphylla di Desa Baletbaru, Kabupaten Jember - Nilasari Dewi; Desy Cahya Widianingrum; Ummi Sholikhah; Ahmad Ilham Tanzil (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Azolla (Azolla microphylla) is a highly nutritious fern that can be used as organic fertilizer and animal feed. As the primary raw material for animal feed, Azolla processing needs to be developed to be durable, have complete nutrition, and have high economic value. The people of Balletbaru Village, who are partners in implementing the assisted village service program, are familiar with Azolla cultivation. However, innovation in processing Azolla crops is needed. This activity aims to form a business group to produce high-nutritional animal feed with Azolla as the main ingredient in Balletbaru village. The series of activities carried out included socialization about the potential use of Azolla as animal feed, training on production and processing techniques of Azolla as animal feed, training on how to prepare highly nutritious animal feed made from Azolla as raw material for ruminants, training in the manufacture of processed feed, training on marketing, monitoring, and evaluation. The results of this community service activity include technology transfer regarding the production of Azolla as an alternative high-nutrition feed where 100% of the community participating in the service program activities can understand and practice making animal feed made from the primary raw material of Azolla. Other outputs are instructions on cultivating and using Azolla as animal feed and products ready to be marketed under the trademark Pazoruso. It is hoped that this product will become an economical source to increase the income and welfare of the service partner community and its surroundings.